Comparative efficacy of oral antibiotics against intracellular populations of uropathogenic Escherichia coli and bladder cell inflammatory response - Michelle Kalu; Peter Jorth; Annie Wong-Beringer (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Abstract Predisposing risks to recurrent urinary tract infections caused by uropathogenic Escherichia coli (UPEC) include the formation of intracellular bacterial communities (IBCs) as a reservoir for persistence within bladder epithelial cells and sustained elevation of proinflammatory mediators that interfere with wound healing. Here we investigated the efficacy of oral agents (nitrofurantoin, doxycycline, and gepotidacin) in intracellular bacterial clearance and proinflammatory signaling in bladder epithelial cell infection in-vitro . Our findings suggested variable and strain-dependent host inflammatory responses to UPEC infection and that mechanistically distinct oral antibiotics differentially affected the expression of proinflammatory mediators (TNFα and PTGS2) and efficacy in clearing intracellular bacteria.